Path Analysis on the Effectiveness of Exclusive Breastfeeding Advocacy Program on Breastfeeding Practice using Theory of Planned Behavior - Valentina Dili Ariwati; Didik Tamtomo; Endang Sutisna Sulaeman (Journal of Health Promotion and Behavior, 2016)
Background: Exclusive breastfeeding coverage was 52.30% in 2015, which was below the national target of 80%. For the past few years Klaten local government has launched the Exclusive Breastfeeding Advocacy Program with the objective to increase exclusive breastfeeding coverage. This study aimed to determine the effectiveness of Exclusive Breastfeeding Advocacy Program using Theory of Planned Behaviour framework.Subjects and Method: This was an analytic observational study with retrospective cohort design. This study was conducted from 2 August to 16 September 2016 in Klaten and Magelang, Central Java, Indonesia. A total of 200 lactating mothers of infants aged 6 to 12 months was selected for this study by multi-stage random sampling. The dependent variables were exclusive breastfeeding and intention. The independent variables were exclusive breastfeeding advocacy program, attitude, subjective norm, and perceived behavior control. The data were collected  using a set of questionnaire, and analyzed by path analysis.Results: The path model showed Goodness of Fit indices as follows: CMIN=4.24, p=0.374, GFI=0.99, NFI=0.99, CFI=1.00, RMSEA=0.017. Strong intention (b=0.15; p <0.001) had direct effect on exclusive breastfeeding. Positive atittude (b = 0.27; p<0.001), positive subjective norm (b=0.26; p <0.001), strong perception of behavior control  (b=0.25; p<0.001), and exclusive breastfeeding advocacy program (b=0.36; p<0.001), had positive effects on intention.Conclusion: Intention has direct effect on exclusive breastfeeding. Atittude toward exclusive breastfeeding, subjective norm, and perception of behavior control, have positive effects on intention. Exclusive breastfeeding advocacy program is effective in increasing the likelihood of providing exclusive breastfeeding.Keywords: exclusive breastfeeding advocacy program, attitude, subjective norm, perceived behavior control, intention, exclusive breastfeeding behavior.Correspondence: Valentina Dili Ariwati. Masters Program in Public Health, Sebelas Maret University.Journal of Health Promotion and Behavior (2016), 1 (3): 149-159https://doi.org/10.26911/thejhpb.2016.01.03.02